Worker Safety Risks Related to Welding Operations for The Manufacturing Industry - Mustafa Kamal, Muhammad Fadlullah; Rozali, Mohd Zulfadli (Research and Innovation in Technical and Vocational Education and Training, 2022)
The safety of workers is a very important aspect to prevent accidents. In the manufacturing industry this problem arises due to employee safety risk factors. The purpose of this study was to identify aspects of worker safety risks associated with welding operations in the manufacturing industry in Batu Pahat, Johor. Identify aspects of safety risks in terms of hazards (hazards), unsafe practices, precautions and the relationship between aspects of safety risks related to workers related to welding operations carried out in the manufacturing industry. This study is quantitative in nature using survey method. Respondents consisting of 75 people selected in this study are from welding workers in five manufacturing industries in Batu Pahat, Johor. The results of the study will be analyzed using Statistical Package for Social Science version 21.0 and the data are analyzed using inferential analysis method (Pearson-r) to find the value of Pearson correlation. Based on the analysis, the Pearson correlation value shows that the relationship between aspects of employee safety risk to hazard (hazard) is 0.820, the relationship between aspects of employee safety risk to unsafe practices is 0.528 and the relationship between aspects of employee safety risk to precautions is 0.383. Overall, based on the findings of the study analyzed, it can be concluded that the employee safety risks associated with welding operations in the manufacturing industry are at the highest level. The results of the study found that employees are aware of employee safety risks and the rules that have been set.